Right to health and encouragement of social participation in elementary education - dos Santos Barbosa, Maria Luiza; Arena Ventura, Carla Aparecida; Liberale, Marina; Hernandez Fernandes, Raquel Helena (Investigación y Educación en Enfermería, 2023)
Objective Develop and validate an ordinary meeting simulation template of the Municipal Health Council applied to students of cycle II of Elementary School. Methods. Qualitative and descriptive research developed in two phases: construction of simulation scenario of ordinary meeting of the Municipal Health Council and validation by committee of experts who analyzed the representativeness and adequacy of the content. The scenario included the items: prebriefing, additional information about the case, scenario objectives, evaluation criteria (observers), scenario duration time, human and physical resources, instructions for the actors, context, references and debriefing. In order to be able to understand which items should be modified according to the evaluations of the experts, it was used as criterion that only items that had 80% or higher percentage of agreement between the experts for modification would be modified. Results: There was agreement to modify the prebriefing in: additional information about the case (100%); learning objectives (88.8%); human and physical resources (88.8%); context (88.8%); and in the debriefing (88.8%). The prebriefing did not reach the level of agreement: evaluation criteria (66.6%), duration of the scenario (77.7%), instruction for authors (77.7%), references (77.7%), which were modified. Conclusion. With the template developed and then validated by the committee of experts, it will be possible to develop in the classroom content related to the right to health and social participation in the scope of elementary education, as well as encourage engagement in important bodies for the maintenance of democracy, justice and social equity.